Climate Changes in the Eastern Mediterranean Sea and their Potential Impacts on the Benthic Fauna in Syria - Ammar, Izdihar (Journal of King Abdulaziz University: Marine Sciences, 2023)
The Syrian marine environment has been experiencing a considerable disturbance in the diversity and distribution of benthic communities, noticeable through visual inspection of coastal rocky substrates, with some species witnessing regression or complete absence, reduced fish catches, and an increase in the dominance of lessesspsian species. These occurrences coincide with a considerable rise in fish prices and other live marine resources. Additionally, the number of alien species has increased and now constitutes more than 25% of the total species count, with some alien species have seen a notable increase and transformation into invasive species within a relatively short time frame. Moreover, there is a notable rise in the number of tropical species of crustaceans and Cnidaria with Atlantic origins. Furthermore, there has been an increase in toxic species and an increase in the annual averages of water temperature and salinity. All of these changes are occurring in parallel with the warming of the Mediterranean Sea and the climate fluctuations experienced in the region since 2016. Field surveys conducted during the months of May, June and July 2023 have documented a mass mortality of the long-spined black sea urchin (Diadema setosum) and a significant decline in the populations of the mussels (Brachidontes pharaonis) in several key locations along the Syrian coastline, both of which are invasive species originating from the Red Sea and the Indian Ocean, against the expansion of alien limpet Cellana eucosmia (Pilsbry, 1892) and alien red algae Hypnea cornuta (Kützing) J.Agardh, 1851. An increase in the number of warm water species is also recorded by documenting the presence of two species of mollusks for the first time in Syria, namely the sea slug Pleurobranchus forskalii Rüppell and Leuckart, 1828, and the purse oyster Isognomon bicolor (C. B. Adams, 1845). These issues are expected to exacerbate in the future, presenting two options: adaptation to the ongoing changes and mitigating the effects of climate change. Researchers and marine scientists have a proactive role to play in raising awareness among the public and local communities about the risks facing marine biodiversity, devising practical solutions, and collaborating with affected sectors to develop governmental policies that aim to achieve sustainable development of marine resources.